Reduction and mutagenic activation of nitroaromatic compounds by a Mycobacterium sp. - Rafii, F (1994)
Mycobacterium sp. strain Pyr-1 cells, which were grown to the stationary phase in media with and without pyrene, were centrifuged and resuspended in a medium containing 1-nitropyrene. Cells that had been grown with pyrene oxidized up to 20% of the added 1-nitropyrene to 1-nitropyrene-cis-9,10- and 4,5-dihydrodiols. However, cells that had been grown without pyrene reduced up to 70% of the 1-nitropyrene to 1-aminopyrene but did not produce dihydrodiols. The nitroreductase activity was oxygen insensitive, intracellular, and inducible by nitro compounds. Nitroreductase activity was inhibited by p-chlorobenzoic acid, o-iodosobenzoic acid, menadione, dicumarol, and antimycin A. Extracts from cells that had been grown without pyrene activated 1-nitropyrene, 1-amino-7-nitrofluorene, 2,7-dinitro-9-fluorenone, 1,3-dinitropyrene, 1,6-dinitropyrene, and 6-nitrochrysene to DNA-damaging products, as shown in Salmonella typhimurium tester strains by the reversion assay and by induction of the umuC gene. Activation of nitro compounds, as shown by the umu test, was enhanced by NADPH. This study shows that Mycobacterium sp. strain Pyr-1 metabolizes nitroaromatic compounds by both oxidative and reductive pathways. During reduction, it generates products that are mutagenic.